PENGARUH MODEL PEMBELAJARAN ROUNDCONSEN (ROUNDTABLE-CONCEPT SENTENCE) TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 1 BERINGIN - Rindy Antika; Khairil Ansari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study was conducted to analyze the extent to which the RoundConsen (RoundTable-Concept Sentence) learning model affects the ability to write explanatory texts of eighth-grade students at SMP Negeri 1 Beringin. The population in this study was all 297 eighth-grade students. The sampling technique was simple random sampling, and two classes were obtained as samples: VIII 2 as the control group and VIII 5 as the experimental group. This study used an experimental approach with an essay test as the instrument. The data analysis technique was quantitative. Based on the results of data processing, it was found that the ability to write explanatory texts with the application of the RoundConsen model produced an average score of 84,06 which is classified as very good. Meanwhile, students who participated in learning with the expository model obtained an average score of 74,06 which is included in the good category. Hypothesis testing using the t-test showed that Thitung (4,78) was greater than Ttabel (2,001), which means there is a significant effect of the application of the RoundConsen model on improving the ability to write explanatory texts of eighth-grade students at SMP Negeri 1 Beringin. Keywords: RoundTable-Concept Sentence Model, Writing, Explanatory Text ABSTRAK Penelitian ini dilaksanakan untuk menganalisis sejauh mana model pembelajaran RoundConsen (RoundTable-Concept Sentence) terhadap Kemampuan Menulis Teks Eksplanasi Siswa Kelas VIII SMP Negeri 1 Beringin. Jumlah populasi dalam penelitian ini adalah seluruh siswa kelas VIII yang berjumlah 297 siswa. Teknik pengambilan sampel dilakukan secara acak sederhana (simple random sampling), dan diperoleh dua kelas sebagai sampel: VIII 2 sebagai kelompok kontrol dan VIII 5 sebagai kelompok eksperimen. Penelitian ini menggunakan pendekatan eksperimen dengan instrumen berupa tes uraian. Teknik analisis data bersifat kuantitatif. Berdasarkan hasil pengolahan data, diperoleh bahwa kemampuan menulis teks eksplanasi dengan penerapan model RoundConsen menghasilkan rata-rata skor sebesar 84,06 yang tergolong dalam kategori sangat baik. Sementara itu, siswa yang mengikuti pembelajaran dengan model ekspositori memperoleh nilai rata-rata sebesar 74,06 yang termasuk dalam kategori baik. Uji hipotesis menggunakan uji-t menunjukkan bahwa Thitung (4,78) lebih besar daripada Ttabel (2,001), yang berarti terdapat pengaruh signifikan dari penerapan model RoundConsen terhadap peningkatan kemampuan menulis teks eksplanasi siswa kelas VIII di SMP Negeri 1 Beringin. Kata Kunci : Model RoundTable-Concept Sentence, Menulis, Teks Eksplanasi